Local global watchdogs: Trade, sourcing and the internationalization of social activism - Pamina Koenig; Sebastian Krautheim; Claudius Löhnert; Thierry Verdier (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2021)
International NGO campaigns criticizing firms for infringements along their internationalized value chains are a salient feature of economic globalization. We argue that understanding the international patterns of NGO campaigns requires accounting for the geography of their targets' economic activities. We propose a model of global sourcing and international trade in which heterogeneous NGOs campaign against heterogeneous firms in response to infringements along their international value chains. We find that campaigns are determined by a triadic gravity equation where all three bilateral trade costs matter for NGO campaigns. Importantly, the sourcing trade costs between the supplier and the firm, which do not involve the country of the NGO, shape the patterns of NGO campaigns through their effect on the sourcing decision of firms. We use recently available data on NGO campaigns to estimate our triadic gravity equation and find strong support for this prediction.
Keywords: F12; F60; F63; L31; O35; 330; international trade; international sourcing; gravity; NGOs; campaigns; social activism